Identifikasi Potensi Wilayah untuk Mendukung Program Penyuluhan Pertanian di Kecamatan Jumo, Kabupaten Temanggung, Provinsi Jawa Tengah - Hanif Fakhri Suryono; Septi Wahyu Wijayanti; Nur Kholilah; Gilang Fadhilah Apriddisa Rasundawa; Sebening Andjar Asmara; Emi Widiyanti (AGRITEXTS: Journal of Agricultural Extension, 2022)
Temanggung Regency has 20 sub-districts and many excellent potentials, including rice, robusta coffee, sugar palm, vanilla and cloves. This substantial potential for development to increase business efficiency, productivity, income and welfare through farming, likewise with agricultural extension activities which are the spearhead of the learning process to improve the welfare of farmers. It is necessary to identify potential areas in extension activities to develop effective and targeted extension programs. For this reason, this study aims to identify the potential of agricultural commodities in Jumo Sub-district, Temanggung Regency using a participatory rural appraisal approach can facilitate the exchange of information between stakeholders to work together in planning the right program. In addition, through location quation (LQ) analysis, it is found that the potential agricultural commodity in Jumo Sub-district is rice for the food crop subsector. In the plantation subsector, there is robusta coffee. It is hoped that the superior commodities of Jumo Sub-district can be further improved by maximizing farming business and can be a reference in making extension programs in Jumo Sub-district, Temanggung Regency.